Zviad Gamsakhurdia’s Foreign Policy - Gabashvili, Manana (Actual Problems of Kartvelology, 2019)
The basis of Zviad Gamsakhurdia’s Foreign Policy was neutrality which meant arranging of relations with all near and far countries. It was restoring connections with the past, with the traditional policy which, situated in the complicated region Geoegia, led during centuries. Such a policy excluded turning Georgia into a polygon by reason of confrontation of great countries. On the countrary, there should have been agreement and mutual cooperation with different forces. Zviad Gamsakhurdia’s prognosis in the interntional politics and his point of views not only came true, but are actual even today and should be taken into consideration. Consequantly, Zviad Gamsakhurdia’s significance is beyond Georgia’s space and a politician he should be studied considerably more thoroughly and in a larger scale.